Avena sativa L. NGB 13390 ... - GLIS Of The ITPGRFA (Nordgen, 2024)
Plant Genetic Resource. Taxonomy: Avena sativa L. Common name(s): Oat Other names: YLITORNIO Conserved by: Nordgen (NORDGEN), Sweden Local sample unique identifier: NGB 13390 Method of creation: Acquisition Date: 1997-05-20 Historical: No Biological status: Traditional cultivar/landrace MLS status: Included ...